Os princípios para o investimento responsável (PRI) e o ativismo dos fundos de pensão - Pereira, Karina Rodrigues (Universidade do Vale do Rio dos Sinos, 2012)
Pension Funds are important institutional investors which hold a large amount of resources from the pension savings of their participants. In order to fulfill its main purpose (future benefit payments), Pension Funds need to invest their resources in the most profitable forms of investment, taking into account the time and the level of risk presented. The Principles for Responsible Investment - PRI were created in order to help them in this issue. The PRI consider that sustainable companies, in terms of environmental, social and corporate governance can generate higher shareholder value in the long run because they are better prepared to face future risks. Whereas Pension Funds can occupy a seat on the board of investee companies, seeking help them on issues addressed by the PRI, the present study has the main objective to analyze the relationship between activism practiced by a Brazilian Pension Fund, PRI signatory, and level of corporate governance and sustainable practices adopted by investees. To conduct this research three statistical models were developed and tested. The first model assesses the relationship between activism and environmental responsibility, the second evaluates the relationship between activism and social responsibility, and the last one evaluates the relationship between activism and corporate governance. Data were collected using the method of documentary research and were obtained from various sources. The sample used in this study was selected from the investment portfolio of PETROS - Petrobras Social Security Foundation, the second largest Pension Fund in Brazil. Forty one companies were considered, observed for a 10-year period (2001 to 2010). The methodology applied to the statistical models regression was the method of Panel Data, with random effects. Finally, the results were calculated and the rates of environmental responsibility, social responsibility and corporate governance of investees were analyzed before and after the presence of the activism of the Pension Fund. The results support the hypothesis that activism practiced by the Pension Funds is positively related to the level of socio-environmental performance and the level of corporate governance of companies in which they invest.
Keywords: Ativismo; Fundos de pensão; Princípios para o investimento responsável; Responsabilidade ambiental; Responsabilidade social; Governança corporativa; Activism; Pension funds; Principles for responsible investment; Environmental responsibility; Social responsibility; Corporate governance; ACCNPQ::Ciências Sociais Aplicadas::Administração